Природа переходов и механизмы генерации в лазерах на основе радиационно легированных кристаллов CdS - Garkavenko, A. S. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The research has shown that the optimum laser transitions in electronic excitation lasers based on radiation doped, optically homogeneous CdS crystals are the transitions from the degenerate conduction band to shallow acceptor levels of palladium and silver isotopes.